The Influence Of Technology Readiness, Professional Development And Teaching Autonomy On Pedagogical Innovation Of Teaching Staffs In Higher Education: Penelitian - Lenny Nuraeni; Firman Aziz; Susatyo Adhi Pramono; Adam Latuconsina; Jaenal Mutakim; Dana Aswadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The research investigation wants to examine the combined impact of Technology Readiness and Professional Development together with Teaching Autonomy on Pedagogical Innovation which instructors implement at universities. The researchers used a quantitative research design to conduct their study which involved surveying 170 university faculty members who had been selected through purposive sampling. The study required respondents to meet three conditions which included being an active lecturer who had worked at least two years while using learning technology and completing professional development training. The research team used multiple linear regression analysis to evaluate their data. The researchers conducted validity and reliability tests together with normality assessment and heteroscedasticity testing and multicollinearity evaluation before they initiated their data analysis procedures. The three variables of Technology Readiness and Professional Development and Teaching Autonomy together with their individual components which cover Pedagogical Innovation showed a positive relationship that reached statistical significance. The research shows that universities can achieve more pedagogical innovation by two actions which develop technological readiness through continuous professional development and provide professors with academic independence during their teaching process. The research aims to develop higher education standards which will benefit Indonesian higher education institutions.